Meningkatkan Kemampuan Bina Diri Menyapu Lantai Melalui Model Direct Instruction bagi Anak Down Syndrome - Hijratul Fajri; Kasiyati Kasiyati (Universitas Negeri Padang, 2023)
The purpose of this study is to prove that the direct instruction model is used to improve the ability to sweep floors for children with Down syndrome. The research form is an A-B-A model experiment with one subject (A-B-A). The data format collected is percentile and analyzed by graphical visual analysis. The results collected from 16 observations in three phases, namely baseline (A1), showed a stable 28.5% and increased (+). The intervention phase (B) obtained stable data of 82% and increased (+). The baseline phase (A2) received a stable 92.2% data. The results showed that the direct instruction model was effectively used to improve floor skills in children with Down syndrome.